2011
DOI: 10.1371/journal.pone.0025056
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Ovarian Cancer Proximal Fluids: Validation of Elevated Peroxiredoxin 1 in Patient Peripheral Circulation

Abstract: BackgroundEpithelial ovarian cancer (EOC) is the deadliest gynecologic malignancy in the United States. Unfortunately, a validated protein biomarker-screening test to detect early stage disease from peripheral blood has not yet been developed. The present investigation assesses the ability to identify tumor relevant proteins from ovarian cancer proximal fluids, including tissue interstitial fluid (TIF) and corresponding ascites, from patients with papillary serous EOC and translates these findings to targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Celis and colleagues [6] investigated proteins from breast cancer and normal TIF, where it was demonstrated that proteins identified by MS-based proteomics could be externally validated in a tissue microarray containing over 70 breast carcinoma tissue samples [10]. Furthermore, there are lots of reports of TIF in renal cell carcinoma, head and neck squamous carcinoma, and ovarian cancer [4,11,12], but there is limited research on TIF in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Celis and colleagues [6] investigated proteins from breast cancer and normal TIF, where it was demonstrated that proteins identified by MS-based proteomics could be externally validated in a tissue microarray containing over 70 breast carcinoma tissue samples [10]. Furthermore, there are lots of reports of TIF in renal cell carcinoma, head and neck squamous carcinoma, and ovarian cancer [4,11,12], but there is limited research on TIF in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Corroboratively to these findings, Prx1 knockout mice showed a higher rate of age-dependent malignancies (163). On the contrary, increased levels of Prxs have, for instance, been described for Prx1 in ovarian cancer proximal fluids (299), and Prx3 in lung cancer (387). Srx and Prx4 promoted the progression of human lung cancer (807).…”
Section: Cancermentioning
confidence: 98%
“…Ascites is fluid in the peritoneal cavity that commonly accumulates in ovarian cancer patients and represents a complex milieu of detached ovarian cancer cells and soluble protein (Gortzak-Uzan et al , 2008; Kuk et al , 2009; Hoskins et al , 2011), whereas TIF is harvested by ex vivo incubation of finely diced solid tumors in buffered solutions (Celis et al , 2005; Teng et al , 2010; Teng et al , 2011). Approximately 60% of the secretome proteins identified from EOC cells in this study have been previously reported from proteomic studies of ascites and/or ex vivo TIF.…”
Section: Resultsmentioning
confidence: 99%